Population-based prevalence of rare diseases in Jeju, Korea: a 2021 analysis using NHIS data - Ki Soo Kang; Jung-Kook Song (Journal of Medicine and Life Science)
This study aimed to investigate the prevalence of rare diseases in Jeju using population-based data. We analyzed 2021 data from the customized research database of the National Health Insurance Service (NHIS). Rare diseases were defined based on the designation of the Ministry of Health and Welfare as of July 1, 2021. The number of patients and claims was calculated. The crude prevalence rate per 100,000 individuals was computed using mid-year population data. Diseases were also classified by hereditary status and by system based on the Korean Standard Classification of Diseases. A total of 4,669 patients with rare diseases were identified. The crude prevalence rate was 696 per 100,000 individuals (619 for males, 774 for females). Among the 30 most frequent diseases, the rates ranged from 51 to 4 per 100,000 individuals. Pediatric prevalence was higher in males, and hereditary diseases were more common in children than in adults (38.1% vs. 15.5%). Medical Aid coverage was observed in 6.0% of patients, indicating greater economic vulnerability. Of the 640 rare diseases identified in the NHIS data (among 1,201 nationally designated diseases), only 279 (44.0%) were observed in Jeju. Rare diseases were less likely to be detected due to the small population of the region. Additionally, 8.3% of patients with rare diseases (excluding ultra-rare diseases and chromosomal abnormalities) and 25.0% of patients with ultra-rare diseases had multiple rare disease diagnoses. This is the first population-based study of the prevalence of rare diseases in Jeju. The findings provide baseline data essential for regional surveillance and policy development.